Effect of glycerol on mechanical and physical properties of silver-chitosan nanocomposite films. Issue 1 (January 2016) - Susilowati, E; Kartini, I; Santosa, S J; Triyono,
Abstract: The effect of using glycerol as plasticizer on mechanical and physical properties of silver-chitosan nanocomposite films have been studied. The nanocomposite films were prepared via three steps consisting of silver-chitosan colloidal nanocomposites preparation, adding of glycerol to colloids and silver-chitosan nanocomposites films formation. During the first step, silver ions were reduced by glucose and accelerated by sodium hydroxide (NaOH). Chitosan of 1% (v/v) act as stabilizing agent. Glycerol with volume variation of 0.2, 0.4, 0.6, 8 and 1.0 mL was added colloidal nanocomposites of 60 mL on the second step. On the third step, colloidal nanocomposites were cast on the polypropylene plate and dried at room temperature. The as-prepared films were then neutralized by NaOH and rinsed with distilled water until the filtrate reached the pH of 7. The colloidal nanocomposites were characterized by UV-Vis spectroscopy and transmission electron microscopy (TEM). The film were characterized by X-ray diffraction (XRD) and thermogravimetric analysis (TGA). The mechanical properties, swelling capacity, water vapor permeability (WVP) of the films were also studied. The results indicated that the addition of different amounts of glycerol on colloidal nanocomposites effects on mechanical and physical properties of the resulted nanocomposite films. The elongation and tensile strength were gradually increased as the glycerol amount. Meanwhile, the swelling capacity, WVP, and crystallinity of the film also showed enhancement at increasing glycerol amount. However, the thermal stability decreased.